El uso de las Tics en la enseñanza de las ciencias sociales en el grado 5 de la Escuela Normal Superior, Sede Resguardo Bajo del municipio de Saboya, Boyacá. (2023)
This research monograph seeks to identify the use of TICS in the teaching of social sciences in the 5th grade of the Escuela Normal Superior, located in the resguardo bajo of the municipality of Saboya, Boyacá. In order to respond to the stated objectives, the perceptions of the students and the fifth grade teacher were taken into account, which were fundamental for the whole research process. Based on this, it was possible to develop the information collection instruments, which included open interviews with the teacher and students, a checklist of the technological tools currently used by the students, and non-participant observation by the researcher.